Perancangan Sistem Informasi Akuntansi Penjualan pada PD Mie Ayam Berkah - Evada Dewata; Rahma Dewi; Yuliana Sari; Hadi Jauhari (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2022)
In this digitalization era, the role of the computer is very important to activate the manual system with all its limitations. The recording of sales transactions at PD Mie Ayam Berkah often errors results in calculations and recording so that the reports of doubtful accuracy. This service is purposed to design the Sales Accounting Information System by utilizing Microsoft Visual Basic 6.0 Program on PD Mie Ayam Berkah in order to help make sales reports more precise, fast, accurate, and relevant. The method used is the interview method and direct review to understand the sales recording system used to design a sales accounting information system. Based on the dedication that has been carried out, it can be concluded that the design of a sales accounting information system at PD Mie Ayam Berkah can simplify the process of recording and reporting transactions so as to produce the information faster and more accurate. In addition, users of the sales accounting information system are also equipped with skills in operating the system so that the sales accounting information system can be properly organized.